Analisa Karakteristik Solar Dengan Kondensat Dari Campuran Plastik dan Pasir Pembentuk Paving Block Melalui Uji Bom Kalorimeter dan Gas Analyzer - Wahyu Dian Krisnanda, I Gede; Suardana, Ngakan Putu Gede; Bandem Adnyana, I Wayan (Teknik Desain Mekanika, 2021)
Abstractt Currently, the increasing use of plastics in society because it has advantages over other materials. But on the other hand, plastic also has disadvantages because the raw material for making plastic comes from petroleum refining which causes depletion of petroleum reserves, several solutions to overcome this include processing it into asphalt, concrete, paving blocks and plastic waste can be processed into fuel oil. This research aims to produce fuel oil products from the condensate resulting from heating gas condensation in the manufacture of paving blocks with plastics LDPE mixed with river sand a variation mixture of 1:5 and 1:7 with a heating temperature of 200oCfor 30 minutes tested with a gas analyzer todetermine the content of CO, CO2, HC and a bomb calorimeter to determine the effect of condensate on the heating value of diesel fuel. From this research, the smaller the amount of sand used in the paving block manufacturing process, the higher the CO, CO2, HC and heating value. Keywords: LDPE plastic, BBM (Fuel oil), heating value